PRINCIPLES AND MODEL FOR THE DEVELOPMENT OF CREATIVE ABILITIES OF PRESCHOOL CHILDREN - Абдужалилова Мадинахон Мухиддин кизи (Galaxy International Interdisciplinary Research Journal, 2023)
The article reveals the features of the system of additional education for children and youth, contributing to the development of creative abilities of preschool children. A model for the development of creative abilities of preschool children is given.